2016
DOI: 10.1038/nutd.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Short-term safety, tolerability and efficacy of a very low-calorie-ketogenic diet interventional weight loss program versus hypocaloric diet in patients with type 2 diabetes mellitus

Abstract: Brackground:The safety and tolerability of very low-calorie-ketogenic (VLCK) diets are a current concern in the treatment of obese type 2 diabetes mellitus (T2DM) patients.Objective:Evaluating the short-term safety and tolerability of a VLCK diet (<50 g of carbohydrate daily) in an interventional weight loss program including lifestyle and behavioral modification support (Diaprokal Method) in subjects with T2DM.Methods:Eighty-nine men and women, aged between 30 and 65 years, with T2DM and body mass index betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
2
28

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(247 citation statements)
references
References 38 publications
8
202
2
28
Order By: Relevance
“…Thirty‐one studies (31/40) reported a total energy prescription, of which 18/31 encouraged an ad libitum intake, 6/31 were moderately energy‐restricted (defined as any set caloric prescription >800 kcal/d that was not weight‐maintaining), 2/31 were severely energy‐restricted (defined as any set caloric prescription ≤800 kcal/d), and 5/31 were adaptive (defined as any caloric prescription that was adjusted according to individual participant progress or diet stage; Table and Table S5). For example, Goday et al used a hypocaloric “active phase” (600‐800 kcal/d) until adequate weight loss was achieved, then progressively increased CHO and energy during a “maintenance stage”. Two other studies using adaptive energy prescriptions were weight‐maintaining by design .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐one studies (31/40) reported a total energy prescription, of which 18/31 encouraged an ad libitum intake, 6/31 were moderately energy‐restricted (defined as any set caloric prescription >800 kcal/d that was not weight‐maintaining), 2/31 were severely energy‐restricted (defined as any set caloric prescription ≤800 kcal/d), and 5/31 were adaptive (defined as any caloric prescription that was adjusted according to individual participant progress or diet stage; Table and Table S5). For example, Goday et al used a hypocaloric “active phase” (600‐800 kcal/d) until adequate weight loss was achieved, then progressively increased CHO and energy during a “maintenance stage”. Two other studies using adaptive energy prescriptions were weight‐maintaining by design .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 15/29 used high‐frequency contact (defined as ≥2 sessions/month), 10/29 used moderate‐frequency contact (defined as ≥1 session/month), and 4/29 used low‐frequency contact (defined as <1 session/month). Five (5/40) studies reported the use of remote contact (eg, email, phone, web‐based application, online discussion boards) for the majority or all of the scheduled contact, or as a supplement to in‐person contact . One study offered participants a choice between remote and/or in‐person contact …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While benefits to low-carbohydrate diets have been described, improvements tend to be in the short term and, over time, these effects are not maintained (74)(75)(76)(77). While some studies have shown modest benefits of very low-carbohydrate or ketogenic diets (less than 50-g carbohydrate per day) (78,79), this approach may only be appropriate for short-term implementation (up to 3-4 months) if desired by the patient, as there is little longterm research citing benefits or harm.…”
Section: Carbohydratesmentioning
confidence: 99%
“…This may be helpful in reducing the need for snacks and large meals. Medical nutrition therapy should be provided to treat co‐morbidities including obesity, dyslipidemia, hypertension and microvascular complications . Regular follow‐up is essential to monitor weight, glycemic control and adherence to the meal plan. Very low‐calorie‐ketogenic (VLCK) diets can be safely and effectively used in the management of young adults with type 2 diabetes . Clinical experience suggests obese older adolescents with type 2 diabetes may also benefit from a carefully monitored VLCK weight loss program.…”
Section: Introductionmentioning
confidence: 99%